Mesoporous silica supported multiple single-site catalysts and polyethylene reactor blends with tailor-made trimodal and ultra-broad molecular weight distributions - Kurek, Alexander Gerhard; Mark, Stefan; Enders, Markus; Kristen, Marc O.; Mülhaupt, Rolf (Macromolecular rapid communications, 2010)
A ternary blend of the bisiminopyridine chromium (III) (Cr-1) with the bisiminopyridine iron (II) (Fe-2) post-metallocenes with the quinolylsilylcyclopentadienyl chromium (III) halfsandwich complex (Cr-3) was supported on mesoporous silica to produce novel multiple single-site catalysts and polyethylene reactor blends with tailor-made molecular weight distributions (MWDs). The preferred cosupporting sequence of this ternary blend on MAO-treated silica was Fe-2 followed by Cr-1 and Cr-3. Cosupporting does not impair the single-site nature of the blend components producing polyethylene fractions with $øverline M _\rm w$ = 104 g · mol−1 on Cr-1, $øverline M _\rm w$ = 3 × 105 g · mol−1 on Fe-2, and $øverline M _\rm w$ = 3 × 106 g · mol−1 on Cr-3. As a function of the Fe-2/Cr-1/Cr-2 mixing ratio it is possible to control the weight ratio of these three polyethylenes without affecting the individual average molecular weights and narrow polydispersities of the three polyethylene fractions. Tailor-made polyethylene reactor blends with ultra-broad MWD and polydispersities varying between 10 and 420 were obtained. When the molar ratio of Fe-2/Cr-1 was constant, the ultra-high molecular polyethylene (UHMWPE, $øverline M _\rm w$ > 106 g · mol−1) content was varied between 8 and 16 wt.-% as a function of the Cr-3 content without impairing the blend ratio of the other two polyethylene fractions and without sacrificing melt processability. When the molar ratio Fe-2/Cr-3 was constant, it was possible to selectively increase the content of the low molecular weight fraction by additional cosupporting of Cr-1. Due to the intimate mixing of low and ultra-high molecular weight polyethylenes (UHMPEs) produced on cosupported single-site catalysts a wide range of melt processable polyethylene reactor blends was obtained.